Aplicación del recurso didáctico digital quizizz para la mejora del aprendizaje de los plurales en inglés - Heredia Albarracín, María José; Paladines Loayza, Ghislayne Belén (Machala : Universidad Técnica de Machala, 2021)
In this research the digital tool Quizizz is implemented as a didactic digital resource, which is very important because when the student interacts with this platform, it improves the learning of the same in addition to being quite creative and fun, with this resource it is achieved that students obtain a significant learning as they reinforce the previously acquired knowledge. Through participant observation, it was determined that students do not differentiate the rules of plurals as they tend to confuse one rule with another. Therefore, the general objective of this research is: To improve the learning of plurals in English through the digital didactic resource Quizizz in the Movers (A1) students of Windsor Academy in the year 2021. It was considered that this research is embodied with the qualitative paradigm through participatory action research in which the researcher is part of and helps in the process to achieve a positive change in the student, for it was taken into account the three students of the Movers level of the educational center Windsor Academy. To collect the necessary information for this research work, we used the methods of participant observation, teacher interview and diagnostic test to the students in order to know their progress in relation to the application of the digital didactic resource Quizizz. It is concluded by elaborating a didactic strategy using the digital platform and thus improve the learning of plurals in English, in addition, the teaching-learning process and Quizizz as a digital didactic resource were theoretically based, therefore, through a diagnostic test it was found that students had very little knowledge and mastery regarding the topic and at the time of the final evaluation it was demonstrated that the application of the didactic strategy was effective.
En la presente investigación se implementa la herramienta digital Quizizz como recurso didáctico, la cual es muy importante ya que cuando el estudiante interactúa con esta plataforma, mejora el aprendizaje de los mismos, además que es bastante creativa y divertida, con este recurso se logra que los estudiantes obtengan un aprendizaje significativo debido a que refuerzan los conocimientos adquiridos previamente. Mediante la observación participante, se determinó que los estudiantes no diferencian las reglas de los plurales ya que suelen confundir una regla con otra. Por ello como objetivo general de esta investigación tenemos: Mejorar el aprendizaje de los plurales en inglés a través del recurso didáctico digital Quizizz en los estudiantes Movers (A1) de Windsor Academy en el año 2021. Se consideró que esta investigación este plasmada con el paradigma cualitativo mediante la investigación acción participativa en el cual el investigador forma parte y ayuda en el proceso para lograr un cambio positivo en el estudiante, para ello se tomó en cuenta a los tres estudiantes del nivel Movers del centro educativo Windsor Academy. Para recolectar la información necesaria para este trabajo de investigación se usó los métodos de observación participante, entrevista a la docente y prueba de diagnóstico a los estudiantes para así conocer su progreso en relación a la aplicación del recurso didáctico digital Quizizz. Se concluye elaborando una estrategia didáctica utilizando la plataforma digital y así mejorar el aprendizaje de los plurales en inglés, además se fundamentó teóricamente el proceso de enseñanza aprendizaje y a Quizizz como un recurso didáctico digital, por ello mediante una prueba de diagnóstico se conoció que los estudiantes tenían muy poco conocimiento y dominio respecto al tema y al momento de realizar la evaluación final se demostró que la aplicación de la estrategia didáctica resultó efectiva.
Keywords: STRATEGY; DIDACTIC RESOURCE; PLATFORM; LEARNING